The Botrytis cinerea aspartic proteinase family - Ten Have, Arjen (2010)
The ascomycete plant pathogen Botrytis cinerea secretes aspartic proteinase (AP) activity. Functional analysis was carried out on five aspartic proteinase genes (Bcap1-5) reported previously. Single and double mutants lacking these five genes showed neither a reduced secreted proteolytic activity, nor a reduction in virulence and they showed no alteration in sensitivity to antifungal proteins purified from grape juice. Scrutiny of the B. cinerea genome revealed the presence of nine additional Bcap genes, denoted Bcap6-14. The product of the Bcap8 gene was found to constitute up to 23% of the total protein secreted by B. cinerea. Bcap8-deficient mutants secreted approximately 70% less AP activity but were just as virulent as the wild-type strain. Phylogenetic analysis showed that Bcap8 has orthologs in many basidiomycetes but only few ascomycetes including the biocontrol fungus Trichoderma harzanium. Potential functions of the 14 APs in B. cinerea are discussed based on their sequence characteristics, phylogeny and predicted localization.